Daily Fluctuation of Planktons Abundance in Percut Sei Tuan Waters, Deli Serdang Regency, North Sumatera - Rafika Rizki; Hesti Wahyuningsih; Ternala Alexander Barus (Postgraduate, University of Mataram, 2023)
Plankton is an aquatic biota that lives following the currents in the water.Â The life of plankton is highly dependent on the water quality in those aquatic environments. The constantly changing physical and chemical conditions of water lead to fluctuations in the abundance of plankton in a water. This study aims to analyze fluctuations in plankton abundance and its correlation with water quality in Percut Sei Tuan Waters. The study was conducted in February and March 2023. Filtration method at 3 stations is the Sampling technique used in this study. The sampling period is carried out in the morning, afternoon, and evening. Data analysis to determine the relationship between variables using Pearson correlation in SPSS version 26. Based on the research results, 42 genera of phytoplankton and 16 genera of zooplankton were found. The highest abundance of phytoplankton was 4.635 Ind/L during the afternoon. The highest abundance of zooplankton was obtained at evening, which was 1.049 Ind/L. This is due to the daily vertical migration of zooplankton and their negative phototactic behavior, while phytoplankton require light for photosynthesis. The research results indicate that the abundance of phytoplankton has a very strong correlation with temperature, light intensity, salinity, TSS, pH, DO, and Nitrate. The abundance of zooplankton is highly correlated with water flow velocity, light intensity, salinity, TSS, TDS, pH, DO, Nitrate, and Phosphate.